2013
DOI: 10.1002/jmrs.29
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy advanced practice – commentary

Abstract: The roles of professionals alter over time according to changing needs and conditions, but can meet opposition when they are seen to intrude upon the domain of other professionals. A growing body of research evidence provides justification of role expansion in radiation therapy into the patient review domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…4 A number of existing and proposed APRT roles were identified. These included roles such as image review, [11][12][13][14][15] treatment review, [15][16][17][18][19][20][21][22][23][24][25][26] breast localisation, 14,27,28 palliative 29-33 and urology. 34 Two conference abstracts note APRT roles at the Peter MacCallum Cancer Centre (PMCC), including imaging, breast, brachytherapy and radiation engineering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A number of existing and proposed APRT roles were identified. These included roles such as image review, [11][12][13][14][15] treatment review, [15][16][17][18][19][20][21][22][23][24][25][26] breast localisation, 14,27,28 palliative 29-33 and urology. 34 Two conference abstracts note APRT roles at the Peter MacCallum Cancer Centre (PMCC), including imaging, breast, brachytherapy and radiation engineering.…”
Section: Resultsmentioning
confidence: 99%
“…The first of these pointed out differences between this and other studies and presenting additional studies which support treatment review APRT roles. 15 The second, from a chief radiation therapist in a centre which has implemented several specialist RT and one APRT role stresses the importance of inter-professional communication, and consultation, particularly with ROs, in developing APRT roles. 25 Research on the palliative APRT role at the Mater Radiation Oncology Centre has provided data on capability and service improvement.…”
Section: Discussionmentioning
confidence: 99%
“…AP in the UK was initially driven by the National Health Service (NHS) [21]. Elsewhere in the world, RTTs as a profession have driven this, striving for it to be documented and evidence based [22,23]. The benefits of role development were recognised as early as 2000 where it was identified that educational strategies were required to allow practitioners to develop and work autonomously [24].…”
Section: United Kingdommentioning
confidence: 99%
“…However, one study examining the scope of radiographic practice in the UK confirmed that the implementation was designed primarily for radiography services. As Cox similarly notes, in the UK “RT AP was more varied and was tailored to suit the needs of individual departments of radiation oncology”. While a number of initiatives displaying the RTT's potential for AP have been developed in Australia and New Zealand, these tend to be “a ‘bottom‐up’ approach, being led by RTs and supported only in certain supportive departments.” Therefore, the CSRT project is one of the first examples of a jurisdiction‐wide, systematic and evidence‐based strategy for the development, implementation and sustainment of an AP role for radiation therapists.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of initiatives displaying the RTT's potential for AP have been developed in Australia and New Zealand, these tend to be "a 'bottom-up' approach, being led by RTs and supported only in certain supportive departments." 9 Therefore, the CSRT project is one of the first examples of a jurisdiction-wide, systematic and evidence-based strategy for the development, implementation and sustainment of an AP role for radiation therapists.…”
Section: Introductionmentioning
confidence: 99%